(untitled) (World Bulletin of Management and Law, 2022)
The current study aims at ascertaining the impact of the behavior that causes informed leadership on organizational silence through the cohesion of the Knowledge teams and on the basis of the literature that focused on the importance of enlightened leadership in a sample of the administrative leaders in the Directorate of Agriculture of Al-Diwaniya, who number 143. Therefore, the study used a number of statistical methods that contributed to determining the essence of the results the study aspires to know about, and perhaps the most prominent of these methods are the arithmetic mean, the standard deviation, the inflation factor, the Pearson correlation factor, and the effect factor. In order to extract results, two packages were used for analysis (SPSS.V.27). Amos.V.26), the results showed that enlightened leadership behaviors (role models, developer, serving, changed, vision, The results also showed that there was an indirect impact of informed leadership through the cohesion of the knowledge teams in the organizational silence, which contributed to improving the mechanisms and capabilities of the administrative leadership at the Directorate of Agriculture in Diwaniya